Respuesta :
Answer:
Step-by-step explanation:
Givens
y2 = y/x
y1 = 1
x2 = 1/y
x1 = 1/x
Formula
m = (y2 - y1) / (x2 - x1)
Solution
m = (y/x - 1) / (1/y - 1/x)
m = ( (y - x)/x ) / ((x - y)/xy)
m = (-(x - y) / x) / ( (x - y) / xy)
Invert the denominator and multiply
m = ( - (x - y) / x ) * x*y / (x - y) Notice x - y cancels.
m = ( - 1 / x ) * (x*y) Notice the xs will cancel.
m = ( - 1 / y) There are no xs anywhere. The slope is - 1/y
Answer: Hello there!
If you have the set of points (x1, y1) and (x2, y2), the slope of the segment whit this endpoints is:
[tex]a = \frac{y2 - y1}{x2 - x1}[/tex]
Now, we have the endpoints (1/x, 1) and (1/y, y/x), the slope of this segment is:
[tex]a = \frac{y/x - 1}{1/y - 1/x}[/tex]
Let's simplify it:
[tex]\frac{y/x - 1}{1/y - 1/x} = \frac{(y-x)/x}{(x - y)/x*y} = \frac{\frac{y-x}{x} }{\frac{-(y-x)}{y*x} }= y*\frac{\frac{y-x}{x} }{\frac{-(y-x)}{x} } = y*(-1) = -y[/tex]
Then the slope of the segment is a = -y, and it does not depend of x